2022
DOI: 10.22363/2313-1683-2022-19-2-382-392
|View full text |Cite
|
Sign up to set email alerts
|

Game Technologies and Gamification Techniques in Teaching English: An Analysis of Pedagogical Experience

Abstract: Game technologies (including computer-based ones) applied for teaching English have long occupied an important and permanent place in the structure of the lesson. They are very helpful in developing intercultural communicative competences as well as increasing motivation and self-organization. The purpose of this study is to objectively show how game methods of work and gamification techniques are actually implemented by modern teachers in English classes in both full-time and distance education. The theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Gamification in learning is like turning lessons into games (Azar & Tan, 2020), (Kovalenko & Skvortsova, 2022). Students earn points for doing well, check a scoreboard to see how they are doing compared to others, work with classmates, and have friendly competitions.…”
Section: Introductionmentioning
confidence: 99%
“…Gamification in learning is like turning lessons into games (Azar & Tan, 2020), (Kovalenko & Skvortsova, 2022). Students earn points for doing well, check a scoreboard to see how they are doing compared to others, work with classmates, and have friendly competitions.…”
Section: Introductionmentioning
confidence: 99%
“…Zaporozhets and a number of other researchers of the mental development of preschool children. Both domestic and foreign authors have convincingly shown that play has a positive impact on the development of higher mental functions (Vygotsky, 1966;Bergen, 2002;Modina, 2008;Kravtsova, Kravtsov, 2017;Fleer, 2022;Kovalenko, Skvortsova, 2022). It has been established that pretend play promotes the development of creativity and thinking, influence the formation of symbolic representation, etc.…”
mentioning
confidence: 99%